2020
DOI: 10.1111/anu.13140
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics analysis of skin coloration of large yellow croaker Larimichthys crocea fed different dietary carotenoids

Abstract: A proteomics analysis was conducted to investigate the effects of dietary carotenoids on the skin coloration of large yellow croaker (Larimichthys crocea) fed diets with different carotenoids for 9 weeks. The diet without carotenoids supplementation was used as the control group (CD). Based on the CD, the other four experimental diets were supplemented with 80 mg/kg of astaxanthin (AST80), 80 mg/kg of xanthophyll (X80), 40 mg/kg of astaxanthin and 40 mg/kg of xanthophyll (AST40 + X40), and 80 mg/kg of astaxant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Similarly, a study on immune response also showed that moderate xanthophyll supplementation markedly increased the concentration of plasma immunoproteins and mRNA expression levels of key regulators involved in the immune response. In the feeding trial of Luo et al. (2020) , five immune and antioxidant stress related proteins (leucocyte cell-derived chemotaxin 2 (LECT2), small ubiquitin-like modifier (SUMO), HSP70, glutathione S-transferase (GST) and charged multivesicular body protein 4C (CHMP4C)) were up-regulated after xanthophyll supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study on immune response also showed that moderate xanthophyll supplementation markedly increased the concentration of plasma immunoproteins and mRNA expression levels of key regulators involved in the immune response. In the feeding trial of Luo et al. (2020) , five immune and antioxidant stress related proteins (leucocyte cell-derived chemotaxin 2 (LECT2), small ubiquitin-like modifier (SUMO), HSP70, glutathione S-transferase (GST) and charged multivesicular body protein 4C (CHMP4C)) were up-regulated after xanthophyll supplementation.…”
Section: Discussionmentioning
confidence: 99%